Drzewa klasyfikacyjne w ocenie wiarygodności kredytobiorców - Staniec, Iwona (Classifying Trees in Evaluation of the Inborrower's Creditworthiness, 2005)
The evaluation by use classifying tree of the credit risk has been presented in this article. It is based on data gained from "Gwarant" company for individual credits on purchase of television set. The test contained 4746 credit contracts. Among them 250 contracts (5,268 %) were not repaid and 4496 contracts (94,732%) were paid off. Therefore a mischievousness was only 5,268 % in analysing test.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 547-555